The Influence of Principal’s Visionary Leadership on the Professional Competence of Teachers at A-Accredited Private Senior High Schools in Pamijahan District, Bogor - Siti Nurfaizah; Muzhir Ihsan; Ima Rahmawati (The Future of Education Journal, 2026)
This study aims to determine the influence of the principal's visionary leadership on the professional competence of teachers in A-accredited private senior high schools across Pamijahan District, Bogor. Methodology: This research employed a quantitative approach with a survey method. The collected numerical data were analyzed using simple linear regression analysis. The data collection technique involved a Likert-scale questionnaire with five response alternatives, consisting of both positive and negative statements. Findings: Based on the results of the regression test, a significance value of 0.000 < α (0.01) was obtained. Consequently, it can be concluded that there is a significant influence of the principal's visionary leadership on teacher professional competence.